The Effect of Photothermal Therapy on Osteosarcoma With Polyacrylic Acid-Coated Gold Nanorods - Su Pan; Hongcun Xing; Xuqi Fu; Hongmei Yu; Zhaogang Yang; Yudan Yang; Wei Sun (SAGE Publishing, 2018)
Background: Polyacrylic acid (PAA)-coated gold nanorods (GNRs) were prepared in this research, and then the structure, stability, temperature increment efficiency, and biocompatibility of GNRs@PAA were detected. Methods: It was demonstrated that GNRs@PAA coupled with an 808 nm laser had superior efficiency of hyperthermia therapy for MG63 human osteosarcoma cell. Results: The mechanism of photothermal therapy of GNRs@PAA was explored, and it was proved that damaged cell membrane and DNA integration caused cell apoptosis and death, and the cell apoptosis rate had been obviously promoted by in vitro photothermal therapy which exhibited time-dose dependence. Conclusion: The results demonstrated that the GNRs@PAA could be a promising candidate for phototherapeutic applications in human osteosarcoma.